Effect of regorafenib in delaying definitive deterioration in health-related quality of life in patients with advanced cancer of three different tumor types - Hofheinz, Ralf-Dieter; Bruix, Jordi; Demetri, George D.; Grothey, Axel; Marian, Marisca; Bartsch, Jennifer; Odom, Dawn (Cancer management and research, 2021)
The objective of this post hoc exploratory analysis was to explore the impact of regorafenib on delaying HRQOL deterioration across three different tumor types.